Measuring PAGI Values in Student Character Development: A Quantitative Study of Universitas PGRI Adi Buana Surabaya - Ayong Lianawati; Budi Purwoko; Muwakhidah Muwakhidah; Ananda Dea Saputri (Ma'soem University, 2025)
This study aims to measure the level of internalization of PAGI character values (Caring, Trustworthy, Persistent, and Innovative) among students at Universitas PGRI Adi Buana Surabaya and to identify implementation challenges in the digital era. Using a descriptive quantitative approach, this research involved a survey of 524 students selected through random sampling. The research instrument was a questionnaire with 76 statement items that was tested for validity and reliability, yielding a Cronbach's Alpha value of 0.960. The results show that the majority of students (76.13%) are in the